FENOMENA PRAKTIK PINJAMAN ONLINE ILEGAL DI INDONESIA: ANALISIS PENEGAKAN HUKUM DAN PERLINDUNGAN KONSUMEN - Baroto, Pandit Dimas; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The phenomenon of illegal online lending practices in Indonesia has become increasingly widespread and troubling for the public, as these platforms operate without licenses and are not registered with the Financial Otoritas Jasa Keuangan (OJK). This study aims to analyze the factors contributing to the growth of illegal online lending practices, examine the forms of legal protection available to victimized consumers, evaluate the roles of OJK and law enforcement authorities, and assess the implementation of existing regulations in addressing illegal online lending. The research employs a normative juridical approach with qualitative analysis of secondary data. The findings reveal that illegal online lending causes significant harm to consumers, particularly due to the lack of transparency in information regarding excessively high interest rates, multiple penalties, short repayment periods, and unlawful debt collection practices. The low level of digital financial literacy among the public, ease of technological access, and limited regulatory supervision are identified as the main factors fostering the proliferation of illegal online lending. Although various regulations have been established, their implementation remains suboptimal. Therefore, stronger synergy between institutions and law enforcement, along with enhanced public education, is required as both preventive and repressive measures against illegal online lending practices. Keywords : illegal online lending, law enforcement, consumer protection, Otoritas Jasa Keuangan Services (OJK), financial technology (fintech)